A multi-period optimization model for the design of an off-grid micro hydro power plant with profitability and degradation considerations - Hernandez, Juan Carlo (Animo Repository, 2020)
Micro hydroelectric power is a clean and efficient source of energy that has been used for the electrification of rural off-grid communities. However, numerous micro hydro installations have failed as caused by factors such as poor site selection and uneconomical design of materials, among others. A multi-period mixed integer linear programming model for the design of an off-grid micro hydro power plant is then developed. The proposed model is able to provide technical specifications such as the penstock dimensions, turbine choice, weir height, and site choice in order to fulfill a community’s demand while simultaneously maximizing the net present value of the investment. The model may choose among different productive end uses, with each being subject to a respective investment cost as well as a set-up time and degradation rate. Computational experiments demonstrate the different capabilities of the model to address real-life scenarios such as population growth and streamflow variability. An increase in energy consumption due to population growth leads to the requirement of a more powerful turbine. Capacity limitations likewise prevent the community to invest in productive end usage. Meanwhile, streamflow variability potentially reduces the capability of the power plant to produce electricity. In these instances, batteries had to simultaneously be used in order to augment the increase in energy requirement. © 2020, Springer Nature Singapore Pte Ltd.